Perancangan Model Kualitas Pelayanan Puskesmas dengan Metode Importance Performance Analysis (IPA) dan Quality Function Deployment (QFD) - Wilujeng, Fuji Rahayu; Rembulan, Glisina Dwinoor (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2019)
The number of Puskesmas in DKI Jakarta Province has increased since 2012 by 288 units to 2016 by 310 units. The increasing number of Puskesmas units does not necessarily make the Puskesmas services adequate. This study aims to measure the factors that influence customer satisfaction and to provide technical responses sourced from Voice of Customer. This study uses the Importance and Performance Analysis method to determine the factors of service quality that affect customer satisfaction, and the Quality Function Deployment method is used to provide a technical response. The results of the analysis using the Importance and Performance Analysis method show that the factors which are of the highest priority are services related to providing appropriate diagnoses by doctors at the Puskesmas, services related to the Puskesmas response to complaints from patients, and service attributes related to the suitability of the drugs provided by doctor at the Puskesmas. Improving responses to patient complaints is a top priority that must be done by the health center to increase patient satisfaction. The technical response in the foremost priority is that medical personnel must provide clear answers about the treatment the patient is undergoing, and doctors at the Puskesmas must be more careful in giving medicines that are appropriate to the patient's illness.